THE EFFECT OF SERVICE FAILURE AND SERVICE RECOVERY ON CUSTOMER SATISFACTION AT BANK SULTRA MAIN BRANCH KENDARI - Azis Muthalib, Dzulfikri; Juharsah, Juharsah; Suleman, Nursaban Rommy; Naim, Ifin; Masse, Ambo (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the simultaneous and partial effects of service failure and service recovery on customer satisfaction at Bank Sultra Main Branch Kendari. The research method used is quantitative with a multiple linear regression approach. Data were collected through questionnaires distributed to 73 respondents and analyzed using F-test, t-test, and coefficient of determination analysis. The results show that service failure and service recovery simultaneously have a significant effect on customer satisfaction. However, partially, only service recovery has a significant influence, while service failure does not show a significant impact. This indicates that customer satisfaction is more influenced by the bank's ability to manage and resolve service failures rather than the failures themselves. These findings support justice theory and previous literature emphasizing the critical role of service recovery in maintaining customer satisfaction.